Efficacy and tolerability of anti-tumour necrosis factor therapy in psoriatic arthritis patients: results from the South Swedish Arthritis Treatment Group register. Issue 3 (20th July 2007) - Kristensen, L E; Gülfe, A; Saxne, T; Geborek, P
Abstract : Background: The use of tumour necrosis factor (TNF) blocking agents in psoriatic arthritis (PsA) is increasing, and the SSATG register has followed patients with PsA for more than 5 years. The aim of the present work therefore was to present efficacy and tolerability data of TNF-blocking agents on PsA in clinical practice, and to study potential predictors for drug survival (the length of time a patient continues to take a particular drug). Materials and methods: Patients (n = 261) with active PsA, starting anti-TNF therapy for the first time in southern Sweden, were included. Basal characteristics, disease activity measures, and termination reason for blockers were prospectively collected during the period April 1999 to September 2006. Cox proportional hazard models were used to investigate predictors for treatment termination. Results: Overall, response rates at 3–12 months for global visual analogue scale (VASglobal50) and pain VAS (VASpain50) were about 50%, whereas response rates for European League Against Rheumatism (EULAR) scoring "overall" and EULAR "good" were around 75% and 55%, respectively. Concomitant methotrexate (MTX) (hazard ratio (HR) 0.64, 95% CI 0.39–0.95, p = 0.03), etanercept (HR 0.49, 95% CI 0.28–0.86, p = 0.01), and high C-reactive protein (CRP) levels (HR 0.77, 95% CI 0.61–0.97, p = 0.03) at treatment initiation were associated with better overall drug survival. The improved drug survival of concomitant MTX appeared to be related to significantly fewer dropouts because of adverse events (HR =  0.24 (0.11–0.52), p<0.01). The blockers were well tolerated with a rate of serious adverse events of 5–6% per year. No unexpected serious adverse events were observed. Conclusion: Concomitant MTX and high CRP levels are associated with treatment continuation of anti-TNF therapy in patients with PsA regardless of joint distribution. The positive effect of MTX was primarily linked to fewer dropouts because of adverse events.